Hot-rolled and annealed ferritic stainless steel sheet and method for producing the same

JP2025014954AActive Publication Date: 2025-01-30JFE STEEL CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023117950
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30
Estimated Expiration
2043-07-20

AI Technical Summary

Benefits of technology

【0008】 シャルピー衝撃試験で得られる靭性は、板厚に対して負の依存性を示すため、同じ組織であっても板厚が薄い鋼板では見かけの靭性が高く出るために、フランジ成型時の割れを適切に評価できない。本発明者らは、靭性の板厚依存性の程度は、式(1)で示される板厚で補正した破面遷移温度(K値)を用いることでよく整理されることを知見した。そして、K値が-20未満で顕著にフランジ成型時の割れが抑制されること、K値を低下させるためには、強い固溶強化元素であるPの固溶量(固溶P量)を0.010%以下とすること、焼鈍後の冷却中に析出するCr濃化相の析出密度を1.0×105個/μm3以下とすることが有効であることを知見した。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014954000001
    Figure 2025014954000001
  • Figure 2025014954000002
    Figure 2025014954000002
Patent Text Reader

Abstract

To provide a hot-rolled and annealed ferritic stainless steel sheet suitable for application to a thick flange, and to provide a method for producing the same.SOLUTION: Provided is a hot-rolled and annealed ferritic stainless steel sheet which has a chemical composition comprising, by mass percent, C: 0.020% or less, Si: 0.01-1.00%, Mn: 0.01-1.00%, P: 0.040% or less, S: 0.010% or less, Al: 0.001-0.100%, Cr: 16.0-19.0%, Ni: 0.01-0.60%, Ti: 0.10-0.40%, N: 0.020% or less, and a balance of Fe and an inevitable impurity, and in which the amount of solute P is 0.010% or less, the precipitation density of the Cr-enriched phase is 1.0×105 particles / μm3 or less, the K value defined by a predetermined formula (1) is less than-20, and the plate thickness is 6.0-10.0 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot-rolled and annealed ferritic stainless steel sheet and a method for producing the same, and more particularly to a hot-rolled and annealed ferritic stainless steel sheet having excellent workability suitable for application to flanges and the like, and a method for producing the same. [Background technology]

[0002] Flanges used in exhaust system parts need to have sufficient corrosion resistance and rigidity. For this reason, flanges made of thick ferritic stainless steel plates (for example, 5 mm or more thick) are used for such exhaust system parts. However, thick ferritic stainless steel plates have low toughness, and cracks occur during flange molding in low-temperature environments, which is a problem that hinders productivity.

[0003] To address these issues, for example, Patent Document 1 discloses a method for producing a Ti-containing ferritic stainless steel sheet having a sheet surface hardness of 170 HV or less by hot rolling a Ti-containing ferritic stainless steel, coiling it at 650 to 800°C, and annealing it at 800 to 1100°C. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-206723 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the present inventors attempted to form flanges using ferritic stainless steel sheets of various thicknesses produced by the process described in Patent Document 1, they found that although the steel sheets had sufficiently low Vickers hardness, cracks sometimes occurred during flange forming, and that this was not necessarily effective in solving the problem. In other words, the ferritic stainless steel sheets according to the conventional technology were not sufficiently effective for application to thick flanges, and further improvement was required.

[0006] An object of the present invention is to provide a hot-rolled annealed ferritic stainless steel sheet suitable for application to thick flanges, and a method for producing the same. [Means for solving the problem]

[0007] The inventors of the present invention have thoroughly investigated the conditions under which cracks occur during flange forming, and have found that a Charpy impact test using a V-notched test piece can be applied to the evaluation. In addition, they have found that when flange forming is performed at a certain temperature, among steel plates having the same Charpy impact value at that temperature but different plate thicknesses, the occurrence of cracks during flange forming increases in the thinner steel plate.

[0008] The toughness obtained by the Charpy impact test shows a negative dependency on the plate thickness, so that a thin steel plate, even if it has the same structure, has a high apparent toughness, and therefore cracking during flange forming cannot be appropriately evaluated. The inventors have found that the degree of the plate thickness dependency of toughness can be well organized by using the fracture appearance transition temperature (K value) corrected by the plate thickness shown in formula (1). They have found that a K value of less than -20 significantly suppresses cracking during flange forming, and that in order to reduce the K value, the amount of solid solution of P, which is a strong solid solution strengthening element (solid solution P amount), should be 0.010% or less, and the precipitation density of the Cr-enriched phase that precipitates during cooling after annealing should be 1.0 x 10 5 pieces / μm 3 It has been found that the following is effective.

[0009] K = vTrs - 50ln(B) (1) Here, vTrs in formula (1) is the fracture appearance transition temperature (°C) obtained by a Charpy impact test, and B is the plate thickness (mm).

[0010] The present invention has been made based on the above findings, and has the following gist. [1] In mass percent, C: 0.020% or less, Si: 0.01 to 1.00%, Mn: 0.01 to 1.00%, P: 0.040% or less, S: 0.010% or less, Al: 0.001 to 0.100%, Cr: 16.0-19.0%, Ni: 0.01 to 0.60%, Ti: 0.10 to 0.40%, and N: 0.020% or less, the balance being Fe and unavoidable impurities, and the amount of solute P is 0.010% or less, The precipitation density of the Cr-enriched phase is 1.0×10 5 pieces / μm 3 is as follows: The K value defined by the following formula (1) is less than -20, A ferritic stainless steel hot-rolled and annealed steel sheet having a thickness of 6.0 to 10.0 mm. K = vTrs - 50ln(B) (1) Here, vTrs in formula (1) is the fracture appearance transition temperature (°C) obtained by a Charpy impact test, and B is the plate thickness (mm). [2] The ferritic stainless steel hot-rolled annealed steel sheet according to [1], wherein the chemical composition further contains, in mass%, one or more selected from the following Group A and Group B: Group A: One or more selected from Cu: 1.00% or less, Mo: 2.00% or less, W: 0.20% or less, Co: 0.20% or less Group B: One or more selected from Nb: 0.10% or less, V: 0.10% or less, REM: 0.100% or less, Mg: 0.0030% or less, Ca: 0.0030% or less [3] A method for producing the ferritic stainless steel hot-rolled annealed steel sheet according to [1] or [2], For a hot-rolled steel sheet having the above-mentioned composition, As the first annealing, annealing is performed under the conditions of an annealing temperature of 700 to 880 ° C. and an annealing time of 3.0 hours or more, and further A method for producing a hot-rolled annealed ferritic stainless steel sheet, comprising the steps of: performing the second annealing under conditions of an annealing temperature of 750 to 880°C, an annealing time of 5 s or more, and an average cooling rate in the temperature range from 700°C to 400°C of 300°C / min or more.

[0011] According to the present invention, it is possible to provide a hot-rolled annealed ferritic stainless steel sheet suitable for application to thick flanges, and a manufacturing method thereof.

[0012] According to the present invention, there is obtained a hot-rolled annealed ferritic stainless steel sheet having excellent toughness and capable of suppressing cracks during punching into thick flanges. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The hot-rolled annealed ferritic stainless steel sheet of the present invention contains, by mass%, C: 0.020% or less, Si: 0.01 to 1.00%, Mn: 0.01 to 1.00%, P: 0.040% or less, S: 0.010% or less, Al: 0.001 to 0.100%, Cr: 16.0 to 19.0%, Ni: 0.01 to 0.60%, Ti: 0.10 to 0.40%, and N: 0.020% or less, with the balance being Fe and unavoidable impurities. The amount of solute P is 0.010% or less, and the precipitation density of the Cr-enriched phase is 1.0×10 5 pieces / μm 3 or less, the K value defined by the following formula (1) is less than −20, and the plate thickness is 6.0 to 10.0 mm.

[0014] K = vTrs - 50ln(B) (1) Here, vTrs in formula (1) is the fracture appearance transition temperature (°C) obtained by a Charpy impact test, and B is the sheet thickness (mm) of the ferritic stainless hot-rolled annealed steel sheet.

[0015] The present invention will be specifically described below.

[0016] First, the chemical composition of the hot-rolled annealed ferritic stainless steel sheet of the present invention will be described. Hereinafter, unless otherwise specified, "%" indicating the content of each component means "mass %".

[0017] C: 0.020% or less C is an element effective in increasing the strength of steel. However, if the C content exceeds 0.020%, toughness and formability are significantly reduced, so the C content is set to 0.020% or less. From the viewpoint of ensuring better toughness and formability, the C content is preferably set to 0.010% or less. The C content is more preferably set to 0.008% or less. Moreover, from the viewpoint of ensuring strength, the C content is preferably set to 0.001% or more. The C content is more preferably set to 0.003% or more.

[0018] Silicon: 0.01 to 1.00% Si is effective in improving the corrosion resistance of the welded portion by concentrating in the oxide film formed during welding, and is also useful as a deoxidizing element in the steelmaking process. These effects are obtained by containing 0.01% or more of Si. However, if the Si content exceeds 1.00%, an increase in the rolling load and significant scale formation in the hot rolling process, and a decrease in pickling ability due to the formation of a Si-enriched layer on the steel sheet surface in the annealing process occur, which is undesirable because it leads to an increase in surface defects and an increase in manufacturing costs. Therefore, the Si content is set to 0.01 to 1.00%. The Si content is preferably 0.05% or more, more preferably 0.10% or more. The Si content is preferably 0.60% or less, more preferably 0.20% or less.

[0019] Mn: 0.01 to 1.00% Mn has the effect of increasing the strength of steel and also acts as a deoxidizer. In order to obtain this effect, a Mn content of 0.01% or more is necessary. However, if the Mn content exceeds 1.00%, the precipitation of MnS, which is the starting point of corrosion, is promoted, and the corrosion resistance decreases. Therefore, the Mn content is set to 0.01 to 1.00%. The Mn content is preferably 0.08% or more. Moreover, the Mn content is preferably 0.60% or less, and more preferably 0.20% or less.

[0020] P:0.040% or less P is an element that is inevitably contained in steel, but since it has a high solid solution strengthening ability, improves the hardness of the matrix, and reduces toughness, it is preferable to reduce it as much as possible. Therefore, the P content is set to 0.040% or less. By reducing the P content, it becomes easier to reduce the amount of solid solution P described below, and it becomes easier to suppress the decrease in toughness, so the P content is preferably 0.030% or less. On the other hand, since excessive de-P increases costs, the P content is preferably 0.010% or more.

[0021] S: 0.010% or less Like P, S is an element that is inevitably contained in steel, but since it is an element that is harmful to corrosion resistance and workability, it is preferable to reduce the content of S as much as possible. In particular, if the S content exceeds 0.010%, the corrosion resistance is significantly reduced. Therefore, the S content is set to 0.010% or less. The S content is preferably 0.006% or less, and more preferably 0.003% or less. There is no particular lower limit for the S content, but since excessive de-S increases costs, the S content is preferably 0.0005% or more.

[0022] Al: 0.001 to 0.100% Al is an effective deoxidizer. Furthermore, since Al has a stronger affinity with nitrogen than Cr, when nitrogen penetrates into a weld, it precipitates as Al nitride instead of Cr nitride, and has the effect of suppressing sensitization. These effects can be obtained by including 0.001% or more of Al. However, if the Al content exceeds 0.100%, the penetration during welding decreases and the welding workability decreases, which is not preferable. Therefore, the Al content is set to 0.001 to 0.100%. The Al content is preferably 0.005% or more, more preferably 0.010% or more. The Al content is preferably 0.060% or less, more preferably 0.040% or less.

[0023] Cr: 16.0~19.0% Cr is the most important element for ensuring the corrosion resistance of stainless steel. If the Cr content is less than 16.0%, sufficient corrosion resistance cannot be obtained in an automobile exhaust gas atmosphere. On the other hand, if the Cr content exceeds 19.0%, precipitation of a Cr-enriched phase occurs significantly during cooling after the first annealing described below, and the hot-rolled annealed sheet becomes significantly embrittled, making it difficult to perform the second annealing, and the desired ferritic stainless steel hot-rolled annealed steel sheet cannot be obtained. Therefore, the Cr content is set to 16.0 to 19.0%. The Cr content is preferably 17.0% or more. Also, the Cr content is preferably 18.5% or less.

[0024] Ni: 0.01 to 0.60% Ni is an element that improves the corrosion resistance of stainless steel, and is an element that suppresses the progress of corrosion in a corrosive environment where a passive film cannot be formed and active dissolution occurs. This effect is obtained by including 0.01% or more of Ni. However, if the Ni content exceeds 0.60%, in addition to reducing workability, stress corrosion cracking is likely to occur. Therefore, the Ni content is set to 0.01 to 0.60%. The Ni content is preferably 0.10% or more. Also, the Ni content is preferably 0.40% or less.

[0025] Ti: 0.10-0.40% In the present invention, Ti is an extremely important element. Ti preferentially bonds with C and N to suppress the precipitation of Cr carbonitrides, lower the recrystallization temperature, and has the effect of suppressing the decrease in corrosion resistance caused by sensitization due to the precipitation of Cr carbonitrides. In order to obtain these effects, it is necessary to contain 0.10% or more of Ti. However, if the Ti content exceeds 0.40%, the amount of solid solution Ti increases excessively, so that coarse Ti carbonitrides are generated in the casting process, causing surface defects, which is not preferable in terms of production. Therefore, the Ti content is set to 0.10 to 0.40%. The Ti content is preferably 0.20% or more. In addition, the Ti content is preferably 0.35% or less. From the viewpoint of the corrosion resistance of the welded portion, it is preferable that the Ti content is set to such that the ratio of the Ti content to the total content of C and N (Ti / (C+N)) satisfies Ti / (C+N)≧8.

[0026] N: 0.020% or less Since N reduces the toughness and formability of steel, the N content is set to 0.020% or less. The N content is preferably set to 0.015% or less. The lower limit of the N content is not particularly limited. However, since excessive denitrification increases costs, the N content is preferably 0.001% or more.

[0027] The basic components (essential components) of the hot-rolled annealed ferritic stainless steel sheet of the present invention have been described above. In the composition of the present invention, components other than those described above (the balance) can be Fe and unavoidable impurities.

[0028] The hot-rolled and annealed ferritic stainless steel sheet of the present invention may further contain one or more elements selected from Cu, Mo, W and Co, each in the range described below.

[0029] Cu: 1.00% or less Cu is an element that is particularly effective in improving the corrosion resistance of the base material and welded parts in an aqueous solution or when weakly acidic water droplets are attached. This effect is obtained by containing 0.01% or more of Cu. Therefore, when Cu is contained, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.10% or more, and further preferably 0.30% or more. However, when Cu is contained in an amount exceeding 1.00%, hot workability may decrease and surface defects may be induced. Furthermore, descaling after annealing may become difficult. Therefore, when Cu is contained, the Cu content is 1.00% or less. The Cu content is preferably 0.60% or less, and more preferably 0.45% or less.

[0030] Mo: 2.00% or less Mo is an element that significantly improves the corrosion resistance of stainless steel. This effect is obtained by containing 0.01% or more of Mo. Therefore, when Mo is contained, the Mo content is preferably 0.01% or more. The Mo content is more preferably 0.30% or more. However, when the Mo content exceeds 2.00%, the rolling load during hot rolling increases and manufacturability decreases. Therefore, when Mo is contained, the Mo content is set to 2.00% or less. The Mo content is preferably 1.40% or less.

[0031] W: 0.20% or less W, like Mo, has the effect of improving corrosion resistance. This effect is obtained by including 0.01% or more of W. Therefore, when W is included, the W content is preferably 0.01% or more. The W content is more preferably 0.05% or more. However, when W is included in an amount exceeding 0.20%, the strength increases, which may lead to a decrease in manufacturability due to an increase in rolling load, etc. Therefore, when W is included, the W content is set to 0.20% or less. The W content is preferably 0.15% or less.

[0032] Co:0.20% or less Co is an element that improves toughness. This effect is obtained by including 0.01% or more of Co. Therefore, when Co is included, the Co content is preferably 0.01% or more. On the other hand, when the Co content exceeds 0.20%, the workability decreases. Therefore, when Co is included, the Co content is set to 0.20% or less.

[0033] The hot-rolled and annealed ferritic stainless steel sheet of the present invention may further contain one or more elements selected from Nb, V, REM, Mg and Ca, each in the range below.

[0034] Nb: 0.10% or less Nb forms carbonitrides with C and N, suppresses sensitization during welding, and improves the corrosion resistance of the welded part. This effect is obtained by containing 0.01% or more of Nb. Therefore, when Nb is contained, the Nb content is preferably 0.01% or more. However, if the Nb content exceeds 0.10%, Fe may be easily dissolved during cooling after the first annealing described later. 2 It is not preferable because Nb precipitates and the toughness decreases. Therefore, when Nb is contained, the Nb content is set to 0.10% or less. The Nb content is preferably 0.05% or less.

[0035] V: 0.10% or less V forms carbonitrides with C and N, suppresses sensitization during welding, and improves the corrosion resistance of welds. This effect is obtained by including 0.01% or more of V. Therefore, when V is included, the V content is preferably 0.01% or more. On the other hand, if the V content exceeds 0.10%, the workability and toughness decrease, which is not preferable. Therefore, when V is included, the V content is set to 0.10% or less. The V content is preferably 0.05% or less.

[0036] REM: 0.100% or less REM (rare earth metals) improve oxidation resistance, suppress the formation of oxide scale, and suppress the formation of Cr-depleted areas directly under the temper color of welding. This effect is obtained when the REM content is 0.0001% or more. Therefore, when REM is contained, the REM content is preferably 0.0001% or more. However, excessive REM content reduces manufacturability such as pickling properties. In addition, an increase in the REM content leads to an increase in manufacturing costs. Therefore, when REM is contained, the REM content is set to 0.100% or less. Note that REM is a general term for Sc, Y, and elements from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, and the REM content here refers to the total content of these elements.

[0037] Mg: 0.0030% or less Mg is an element effective in improving the equiaxed crystal ratio of the slab and improving the workability and toughness. Furthermore, in a steel containing Ti as in the present invention, the toughness decreases when the Ti carbonitrides become coarse, but Mg also has the effect of suppressing the coarsening of the Ti carbonitrides. These effects can be obtained by containing 0.0002% or more of Mg. Therefore, when Mg is contained, the Mg content is preferably 0.0002% or more. On the other hand, when the Mg content exceeds 0.0030%, the surface properties of the steel are deteriorated. Therefore, when Mg is contained, the Mg content is set to 0.0030% or less. The Mg content is preferably 0.0004% or less.

[0038] Ca:0.0030% or less Ca is an effective component for preventing nozzle clogging due to the crystallization of Ti-based inclusions, which is likely to occur during continuous casting. This effect can be obtained by including 0.0002% or more of Ca. Therefore, when Ca is included, the Ca content is preferably 0.0002% or more. However, when Ca is included in an amount exceeding 0.0030%, the corrosion resistance decreases due to the formation of CaS. Therefore, when Ca is included, the Ca content is set to 0.0030% or less. The Ca content is preferably 0.0010% or less.

[0039] Solid solution P amount: 0.010% or less An important feature of the ferritic stainless steel hot-rolled annealed steel sheet of the present invention is that the amount of solute P is 0.010% or less. P is an element with high solution strengthening ability, and solute P increases the strength of the stainless steel sheet and decreases its toughness. Therefore, it is preferable that the amount of solute P is as low as possible, and by making the amount of solute P 0.010% or less, the toughness is significantly improved. Therefore, the amount of solute P is set to 0.010% or less. The amount of solute P is preferably 0.005% or less. The amount of solute P is determined by the method described in the examples.

[0040] Precipitation density of Cr-enriched phase: 1.0×10 5 pieces / μm 3 below An important feature of the ferritic stainless steel hot-rolled annealed steel sheet of the present invention is that the precipitation density of the Cr-enriched phase is 1.0×10 5 pieces / μm 3 The following points should be noted. The Cr-enriched phase is a Cr-enriched phase that precipitates when a stainless steel sheet is held in the range of 400 to 500°C, and is known as the phase that causes the 475°C embrittlement that is characteristic of ferritic stainless steels. The precipitation of the Cr-enriched phase increases the strength of the matrix and reduces its toughness. For this reason, it is preferable that the precipitation density of the Cr-enriched phase is as low as possible, and should not exceed 1.0×10 5 pieces / μm 3 The toughness is dramatically improved by making the Cr concentration below 1.0×10 5 pieces / μm 3 The precipitation density is preferably 0.5×10 5 pieces / μm 3 The precipitation density of the Cr-enriched phase is determined by the method described in the Examples.

[0041] K value: less than -20 The ferritic stainless steel hot-rolled annealed steel sheet of the present invention has a K value defined by the above formula (1) of less than -20. As described above, a Charpy impact test using a V-notched test piece can be applied to evaluate cracks caused by flange forming. However, the toughness obtained by the Charpy impact test shows dependency on the plate thickness, so that cracks during flange forming cannot be appropriately evaluated from the toughness obtained by the Charpy impact test. Therefore, in the present invention, the K value defined by the above formula (1) was used, which takes into account the degree of dependency of toughness on plate thickness. If the K value is less than -20, cracks during flange forming can be significantly suppressed. The K value is preferably -50 or less.

[0042] Plate thickness: 6.0~10.0mm If the plate thickness is less than 6.0 mm, the toughness required for flange forming can be expected even without applying the present invention, while if the plate thickness exceeds 10.0 mm, sufficient toughness required for flange forming cannot be obtained even if the present invention is applied. Therefore, the plate thickness range to which the present invention is applied is set to 6.0 to 10.0 mm. By setting the plate thickness to 6.0 to 10.0 mm, the effect of the present invention can be enjoyed more. The plate thickness is preferably 7.0 mm or more. Also, the plate thickness is preferably 9.0 mm or less.

[0043] Next, the method for producing the hot-rolled annealed ferritic stainless steel sheet of the present invention will be described.

[0044] First, molten steel having the above-mentioned composition is produced by a known method such as a converter, an electric furnace, or a vacuum melting furnace, and then made into a steel material (slab) by a continuous casting method or an ingot making-blooming method.

[0045] Next, the above steel material is hot-rolled to obtain a hot-rolled steel sheet. Hot-rolling may be performed according to a conventional method up to finish rolling. The preferred manufacturing conditions are as follows. Stainless steel having the above-mentioned composition is melted and cast, then heated to 1100 to 1300°C, and hot-rolled at a finish temperature of 700 to 1000°C and a coiling temperature of 400 to 750°C to obtain a hot-rolled steel sheet having a thickness of 6.0 to 10.0 mm.

[0046] First annealing: Annealing temperature: 700-880℃, Annealing time: 3.0 hours or more Next, the hot-rolled steel sheet obtained above is subjected to a first annealing. In the present invention, the first annealing is an important process in which the amount of solute P is reduced by precipitating the solute P as FeTiP, the structure after the second annealing described later is softened, and the hot-rolled structure is also recrystallized. If the annealing temperature is less than 700°C or the annealing time is less than 3.0 hours, the precipitation of FeTiP is insufficient, and the amount of solute P cannot be reduced to 0.010% or less. Furthermore, since the recrystallization is also insufficient, the structure after the second annealing cannot be softened, and the K value cannot be reduced to less than -20. On the other hand, if the annealing temperature exceeds 880°C, although the recrystallization is sufficient, FeTiP is re-dissolved, the amount of solute P cannot be reduced to 0.010% or less, and the K value cannot be reduced to less than -20 even after the second annealing. Therefore, in the first annealing, the annealing temperature is set to 700 to 880°C, and the annealing time is set to 3.0 hours or more. The annealing temperature is preferably 800° C. or higher, and more preferably 810° C. or higher. The annealing temperature is preferably 860° C. or lower, more preferably 840° C. or lower, and further preferably 820° C. or lower. Although there is no particular upper limit for the annealing time, if the annealing time is less than 100 hours, the crystal grains become coarse, which makes it easier to suppress a decrease in toughness, and therefore, the annealing time is preferably less than 100 hours.

[0047] Second annealing Annealing temperature: 750 to 880°C, annealing time: 5 seconds or more The steel sheet after the first annealing is cooled to below the annealing temperature range of the first annealing (below 700 ° C). In order to prevent excessive load from being applied to the manufacturing equipment, the steel sheet after the first annealing is preferably cooled to 300 ° C or less. The cooling rate and other conditions at this time are arbitrary. In the steel sheet obtained by the first annealing, a small amount of Cr-enriched phase is precipitated in a spherical shape during the cooling process, causing embrittlement and hardening. By further performing the second annealing on the steel sheet subjected to the first annealing, the precipitated Cr is re-dissolved, further softening occurs, and the toughness can be improved. As the second annealing, the annealing temperature is set to 750 ° C or more and the annealing time is set to 5 s or more, so that the precipitated Cr can be re-dissolved. On the other hand, if the annealing temperature exceeds 880 ° C, FeTiP is dissolved, the amount of solute P exceeds 0.010%, and the toughness is reduced. Therefore, in the second annealing, the annealing temperature is 750 to 880°C, and the annealing time is 5 seconds or more. The annealing temperature is preferably 770°C or more, and more preferably 800°C or more. The annealing temperature is preferably less than 870°C, and more preferably less than 860°C. The annealing time is preferably 15 seconds or more. There is no particular upper limit to the annealing time, but if it is 360 seconds or less, it is easy to suppress a decrease in toughness due to grain coarsening, so the annealing time is preferably 360 seconds or less.

[0048] Average cooling rate in the temperature range from 700℃ to 400℃: 300℃ / min or more Cr redissolved by the second annealing will precipitate again if the cooling rate after the second annealing is slow. This Cr reprecipitation can be suppressed by setting the cooling time in the temperature range from 700°C to 400°C to 1 min or less. Therefore, in the present invention, the average cooling rate in the temperature range from 700°C to 400°C is set to 300°C / min or more. There is no particular upper limit to the average cooling rate, but as an example, the average cooling rate is 2000°C / min or less.

[0049] The above steps provide the hot-rolled annealed ferritic stainless steel sheet of the present invention. The obtained hot-rolled annealed steel sheet may be descaled by shot blasting or pickling as necessary. In addition, grinding, polishing, etc. may be performed to improve the surface properties. The hot-rolled annealed steel sheet provided by the present invention may then be annealed, cold-rolled, and cold-rolled sheet annealed. EXAMPLES

[0050] The present invention will now be described in detail with reference to examples.

[0051] The stainless steel melt having the composition shown in Table 1 was melted in a 150 ton converter and refined by strong stirring and vacuum oxygen decarburization (SS-VOD), and was continuously cast into a steel slab having a width of 1000 mm and a thickness of 200 mm. The steel slab was heated at 1200°C for 1 hour, and then subjected to reverse rough rolling using three stands as hot rolling to obtain a steel sheet having a thickness of about 40 mm, which was then further subjected to tandem finishing rolling using seven stands to obtain a hot-rolled steel sheet having a thickness of 6.0 mm to 8.0 mm. The obtained hot-rolled steel sheet was subjected to annealing shown in Table 2 to obtain a ferritic stainless steel hot-rolled annealed steel sheet.

[0052] The obtained hot-rolled annealed ferritic stainless steel sheets were evaluated as follows.

[0053] (1) Evaluation of the amount of solute P After the second annealing (after the first annealing for No. 11 and No. 20 in Table 2, which were not subjected to the second annealing), analysis samples of 50 mm square were taken from a total of four locations, namely, the center position of the sheet width and a position 200 mm in the width direction from the width end portion, at the front and rear ends of the steel sheet (coil). The amount of solute P was evaluated for each sample by the following procedure, and the average value was taken as the amount of solute P.

[0054] The amount of dissolved P can be determined by the following procedure. The total P content was measured in accordance with JIS G 1214:1998 Iron and steel - phosphorus determination method. That is, the analysis sample was dissolved in a mixed acid of hydrochloric acid, nitric acid, and perchloric acid, and the phosphorus was converted to orthophosphoric acid by perchloric acid white smoke treatment, after which a complex was formed with molybdic acid, and the amount of P (P1) in the solution was quantified by molybdophosphoric acid blue (molybdenum blue) absorptiometry. Total P content (mass%) = (P1 / mass of analytical sample) × 100

[0055] The amount of deposited P (mass%) was measured as follows: The analysis sample was subjected to constant current electrolysis (current density ≦20 mA / cm) using an acetylacetone-based electrolyte (AA solution). 2 ) The electrolytic residue in this electrolytic solution is filtered using a membrane filter with a pore size of 100 nm. The filtered electrolytic residue is then dissolved in a mixed acid of hydrochloric acid, nitric acid, and perchloric acid, and treated with white smoke from perchloric acid to convert phosphorus to orthophosphoric acid, after which a complex is formed with molybdic acid, and the amount of P (P2) in the solution is quantified using molybdophosphoric acid blue (molybdenum blue) absorptiometry. Amount of precipitated P (mass%) = (P2 / mass of analytical sample) x 100 The amount of dissolved P is obtained by subtracting the amount of precipitated P from the total amount of P analyzed by the above method.

[0056] (2) Evaluation of precipitation density of Cr-enriched phase After the second annealing (after the first annealing for No. 11 and No. 20 in Table 2, which did not undergo second annealing), analysis samples measuring 50 mm square were taken from a total of four locations, namely, the center of the sheet width and a location 200 mm in the width direction from the width end, at the front and rear ends of the steel sheet (coil). The precipitation density of the Cr-enriched phase was evaluated for each sample using the following procedure, and the average value was taken as the precipitation density of the Cr-enriched phase.

[0057] In the present invention, the Cr-enriched phase is a particle (particulate region) that appears when an isoconcentration surface with a Cr concentration of 28 mass% is drawn by performing a three-dimensional atom probe analysis of an analysis sample. The precipitation density of the Cr-enriched phase is obtained by the following procedure. After mirror polishing, an analysis sample is electrolytically polished to a thickness of 50 μm or more. A needle-shaped sample with a width of 100 nm is prepared from within a crystal grain near the half-thickness position using a focused ion beam, and is subjected to three-dimensional atom probe analysis. The needle-shaped sample is observed in advance using a scanning transmission electron microscope. The sample diameter obtained there is matched to the sample diameter measured by the three-dimensional atom probe analysis, thereby determining the scale of the measurement results by the three-dimensional atom probe analysis. For the three-dimensional atom probe analysis, a LEAP4000XSi manufactured by AMETEK is used, and measurements are performed on an area of ​​50 nmφ×50 nm or more. The irradiated laser has a wavelength of 355 nm, a laser power of 20 pJ, and a pulse rate of 500 kHz. The temperature of the needle-shaped sample is kept at 50 K during the measurement. The measured data was analyzed using AMETEK's IVAS software, which selects mass spectrum peaks so as not to include mass interference, and analyzes the detected elements. The precipitation density of the Cr-rich phase was obtained by counting the particles that appeared when drawing an isoconcentration surface of a Cr concentration of 28 mass% in an analysis target area of ​​30 x 30 x 120 nm that does not include measurement artifacts (noise), as the Cr-rich phase. Note that Cr-rich phases with a maximum diameter of 1.0 nm or less were considered to be noise that may appear in the analysis, and were excluded from the count.

[0058] (3) Evaluation of K value After the second annealing (No. 11 and No. 20 in Table 2, which were not subjected to the second annealing, were subjected to the first annealing), a V-notch Charpy impact test piece conforming to JIS Z 2242:2018 was taken from a total of four locations, namely, the center position of the sheet width and a position 200 mm from the width end in the width center direction, at the front and rear ends of the steel sheet (coil). The V-notch was taken in the direction perpendicular to the rolling direction. The thickness of the test piece was the same as that of the steel sheet, and no thickness adjustment was performed. The Charpy impact value and brittle fracture rate of the test piece were determined in accordance with JIS Z 2242:2018. vTrs was calculated according to the method specified in Appendix D of the JIS. That is, the brittle fracture rate was fitted with a hyperbolic tangent function, and the temperature at which the fitted brittle fracture rate was 50% was set, and the average value of the four test locations was used for evaluation. Using this vTrs (℃) and the average plate thickness B (mm) of the test pieces, the K value was calculated using the following formula (1). A K value of -50 or less was rated as ⊚ (pass, particularly excellent), less than -20 was rated as ◯ (pass), and -20 or more was rated as × (fail). K = vTrs - 50ln(B) (1) Here, in formula (1), vTrs is the fracture appearance transition temperature (°C) obtained by the Charpy impact test, and B is the plate thickness (mm).

[0059] The test results are shown in Table 2 together with the annealing conditions.

[0060] [Table 1]

[0061] [Table 2]

[0062] As shown in Table 2, Nos. 1 to 10, whose steel composition and annealing conditions fall within the ranges of the present invention, all have a K value of less than -20 and have excellent toughness.

[0063] In contrast, in No. 11, which had a Cr content exceeding the range of the present invention, significant embrittlement due to Cr precipitation occurred during the cooling process after the first annealing, and cracks occurred during the second annealing, making it impossible to evaluate. In No. 12, in which the annealing temperature of the first annealing was below the range of the present invention, the amount of solute P could not be sufficiently reduced, and the specified K value could not be obtained even though the second annealing conditions were appropriate. In No. 13, in which the annealing temperature of the first annealing was above the range of the present invention, FeTiP re-dissolved during the first annealing, and the amount of dissolved P could not be reduced. As a result, the specified K value could not be obtained even though the second annealing conditions were appropriate. In No. 14, in which the annealing time of the first annealing was below the range of the present invention, the amount of dissolved P could not be sufficiently reduced due to the short annealing time of the first annealing, and the predetermined K value could not be obtained even though the second annealing conditions were appropriate.

[0064] In No. 15, in which the annealing temperature of the second annealing was above the range of the present invention, FeTiP re-dissolved during the second annealing, and the amount of dissolved P could not be reduced. As a result, the specified K value could not be obtained even though the first annealing conditions were appropriate. In No. 16, in which the annealing temperature of the second annealing was below the range of the present invention, the Cr precipitates could not be redissolved during the second annealing, and the specified K value could not be obtained even though the first annealing conditions were appropriate. In No. 17, in which the annealing time of the second annealing was below the range of the present invention, the Cr precipitates could not be redissolved during the second annealing, and the specified K value could not be obtained even though the first annealing conditions were appropriate. In No. 18, in which the average cooling rate in the temperature range from 700°C to 400°C in the second annealing was below the range of the present invention and the cooling time in the said temperature range exceeded 1 min, the cooling was slow, so that Cr precipitates were precipitated again during cooling, and the specified K value could not be obtained even though the first annealing conditions were appropriate.

[0065] In No. 19 in which the first annealing was omitted, the amount of solute P could not be reduced during the second annealing, and the desired K value could not be obtained even though the second annealing conditions were within the range of the present invention. In the case of No. 20, in which the second annealing was omitted, the required K value was not obtained due to Cr precipitates that precipitated during cooling in the first annealing.

[0066] In this embodiment, the flanges were formed using Nos. 1 to 10, which had a predetermined K value and excellent toughness. Specifically, the outer and inner circumferences were press-punched while controlling the temperature of the workpiece to 0°C ± 5°C, and then cut to form an oval flange shape with an inner diameter of 30 mmφ, a minor axis diameter of 80 mm, and a major axis diameter of 120 mm. As a result, the flanges were formed without cracking for all of Nos. 1 to 10. On the other hand, when the flanges were formed in the same manner as above using Nos. 11 to 20, which did not show the predetermined K value, as the workpiece, cracks occurred from the ends of the sheared surfaces during the press-punching process, and none of them could be formed into a flange without cracking.

Claims

1. In mass percent, C: 0.020% or less, Si: 0.01-1.00%, Mn: 0.01-1.00%, P: 0.040% or less, S: 0.010% or less, Al: 0.001-0.100%, Cr: 16.0-19.0%, Ni: 0.01 to 0.60%, Ti: 0.10 to 0.40%, and N: 0.020% or less, the balance being Fe and unavoidable impurities; and the amount of solute P is 0.010% or less; The precipitation density of the Cr-enriched phase is 1.0×10 5 pieces / μm 3 is as follows: The K value defined by the following formula (1) is less than −20, A ferritic stainless steel hot-rolled annealed steel sheet having a thickness of 6.0 to 10.0 mm. K=vTrs-50ln(B)...(1) Here, vTrs in formula (1) is the fracture appearance transition temperature (°C) obtained by a Charpy impact test, and B is the plate thickness (mm).

2. The ferritic stainless steel hot-rolled annealed steel sheet according to claim 1, wherein the component composition further contains, in mass%, one or more elements selected from the following Group A and Group B. Group A: one or more selected from Cu: 1.00% or less, Mo: 2.00% or less, W: 0.20% or less, Co: 0.20% or less Group B: One or more selected from Nb: 0.10% or less, V: 0.10% or less, REM: 0.100% or less, Mg: 0.0030% or less, and Ca: 0.0030% or less

3. A method for producing the ferritic stainless steel hot-rolled annealed steel sheet according to claim 1 or 2, For a hot-rolled steel sheet having the above-mentioned composition, As the first annealing, annealing is performed under the conditions of an annealing temperature of 700 to 880 ° C. and an annealing time of 3.0 hours or more, and further The second annealing is performed under the conditions of an annealing temperature of 750 to 880 ° C., an annealing time of 5 s or more, and an average cooling rate in the temperature range from 700 ° C. to 400 ° C. of 300 ° C. / min or more.

Citation Information

Patent Citations

  • Ferritic stainless steel with excellent formability and manufacturing method thereof

    CN101538683A

  • Ferritic single phase stainless steel slab, and method for producing ferritic single phase stainless steel slab

    JP2011168866A

  • Ferritic stainless steel hot rolled steel sheet for flange and manufacturing method therefor

    JP2017095789A

  • Ti-CONTAINING FERRITIC STAINLESS STEEL SHEET GOOD IN TOUGHNESS

    JP2017172002A

  • Ferritic stainless steel hot-rolled plate and method for manufacturing the same and ferritic stainless cold-rolled plate

    JP2022150255A